Advancements in PET bottle plastic slitting devices for raw material 3D printing filament production - Utama, D.W.; Hagai, H.; Halim, A.; Chan, G. (Universitas Mataram, 2025)
The world is facing a significant environmental challenge due to the accumulation of plastic waste, especially PET (Polyethylene Terephthalate) bottles. Indonesia is no exception to this problem. Every year, millions of tons of PET bottles are produced, and most of them end up as waste that takes a long time to decompose. This study aims to investigate the technical and engineering aspects involved in creating a slitting device for PET bottle plastic, which will be used as raw material for Fused Deposition 3D printer filament. The research will focus on overcoming the challenges associated with producing consistent and high-quality raw materials filament and exploring innovative solutions and advancements in filament material design. The slitting device is designed to produce plastic strips with a consistent width of 10 mm and a tolerance of ±1 mm, using easily accessible cutting blades. Ensuring a consistent strip width is crucial for producing 3D printing raw material filament with a diameter of 1.75 mm and a tolerance of ±0.05 mm. Two versions of the slitting design, version 1 and version 2, were tested, and improvements were made to reduce friction and optimize cutting efficiency, resulting in consistent strip width. The second version performed better, producing longer, more uniform strips with lower pulling force. These strips are then proposed to be processed for 3D printing filament, demonstrating the potential of this tool to transform PET bottle waste into valuable raw materials